Blockchain and AI Technology Convergence: Applications in E-Commerce - Suradi, Agustinus (Yayasan Gema Bina Nusantara, 2024)
The discovery of blockchain technology is considered capable of increasing data and transaction security. Everything recorded cannot be altered or changed retrospectively, making blockchain secure. Blockchain technology and artificial intelligence can be applied to various aspects, but this research review focuses on blockchain technology and artificial intelligence for e-commerce. E-commerce is buying or selling goods or services via a computer network. Currently, e-commerce has developed so rapidly that it has diverse business models and a variety of goods and services offered. E-commerce makes it easy to carry out transactions, but apart from all this, there are security problems in e-commerce transactions. This research aims to help future research by reviewing, organizing, analyzing, and synthesizing the application of blockchain technology and artificial intelligence to e-commerce. The method used in this research adopted the Kitchenham literature review method, which consists of three stages: planning, implementing, and reporting the review. The collection of articles is distilled into relevant articles about developments in blockchain technology and artificial intelligence for e-commerce. The results of this research are in the form of a summary of predictions that the use of blockchain in e-commerce will increase secure data related to transactions and feedback in e-commerce.